A good name needs to be found : a philosophical investigation of Paralympic and Olympic co-operation. (Final report submitted to the IOC Olympic Studies Centre in the framework of the PhD Students Research Grant Programme 2015) - Waddell, M. (University of Western Ontario, London, Ontario, 2016)
Summary: The work of the International Paralympic Committee (and its predecessors) with the International Olympic Committee to establish the Paralympic Games as an event twinned with the Olympic Games has been instrumental in promoting access to competitive sporting opportunities for athletes with disabilities around the globe. This project examines the relationship between these two organizations to illustrate the difficulties that come with maintaining para-sport as an event separate from able-bodied competitions. Although it has been a source of much growth, the close relationship of the Olympic and Paralympic Games, and the vast power difference between them, has resulted in the Paralympic Games struggling to establish a viable identity of its own. This situation can be ameliorated by adjusting the current `one bid, one city` policy towards an even more integrated event that includes both able-bodied and para athletes. Support for this recommendation will be provided by a philosophical examination of the importance of inclusion and an inquiry into how the right of free speech can inform sport practice.